Family language policy in bilingual Finnish and Swedish families in Finland - Huhta, Austin (2020)
In Finland families are only allowed to choose one language for their child to be the child’s L1 even if the family is bilingual. With both Finnish and Swedish being national languages of Finland this thesis looked into which language a family chose, why they chose it, and how they helped their child maintain it. Looking at their perspective on this can allow us to get further insight into family language policy in Finland. The research method used here is a case study, with semi-structured interviews for the data collection and interpretive phenomenological analysis for the data analysis. This thesis interviewed a bilingual family with a Finn and a Swedish Swede and their one child. It found that while their initial language choice was Swedish, that their family language policy was dynamic. Over time the child was switched from Swedish medium education to Finnish medium education; however, at home multiple family language policies worked together to help maintain his Swedish language skills. The findings demonstrated that the right combination of family language policies and more formal educational settings can work together to help children grow up to be bilingual even if the minority language is mainly used at home. It is recommended that future research in this area continues to expand the number of research participants, and also uses more research participants from different backgrounds.